Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pengguna Jasa Pengiriman Barang Pada PT. Pos Indonesia Tbk Unit Kalukku Kecamatan Kalukku Kabupaten Mamuju - Asia, Nur; Musyawarah, Irdha Yanti; Jasriani, Jasriani; Kadir, Selvi Juniarni (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2024)
This research aims to determine the effect of service quality on user satisfaction of goods delivery services at PT Pos Indonesia Tbk Kalukku Unit, Mamuju Regency. The type of data used in this research is quantitative. This research uses multiple linear regression analysis to calculate the quantitative impact of each variable on changes in events (variable X) then carries out partial tests and simultaneous tests. The results of the research show that the reliability variable has a significant effect on user satisfaction of goods delivery services at PT Pos Indonesia Tbk Kalukku Unit, Mamuju Regency. The responsiveness variable has a significant effect on user satisfaction with goods delivery services at PT. Pos Indonesia Tbk, Kalukku Unit, Mamuju Regency. The empathy variable has a significant effect on user satisfaction with goods delivery services at PT. Pos Indonesia Tbk, Kalukku Unit, Mamuju Regency. The guarantee variable has a significant effect on user satisfaction of goods delivery services at PT. Pos Indonesia Tbk Kalukku Unit, Mamuju Regency and the physical evidence variable have a significant effect on user satisfaction with goods delivery services at PT. Pos Indonesia Tbk, Kalukku Unit, Mamuju Regency. The most dominant responsiveness variable influences user satisfaction with goods delivery services at PT Pos Indonesia Tbk Kalukku Unit, Mamuju Regency.